(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
This article examines the sentence delivered by Colombia’s Constitutional Court C-055/2022. With this decision, the Court partially decriminalizes the crime of abortion provided by Art. 122 of Colombia’s Criminal Code, which was sanctioned in all circumstances except those indicated in the same provision. These exceptions, which already indicated a certain openness to the recognition of women’s sexual and reproductive rights, were included through the decision of Court C-355 of 2006. The comment addresses the evolution of the Court’s decisions and the reasons for the partial decriminalization of article 122 of the Criminal Code: from socio-cultural development, as represented by the various regional pro-voluntary abortion movements, to the need for consistent legislation at all levels, whether national, regional, or international.